Actions of noradrenaline and acetylcholine on sympathetic ganglion cells - Kobayashi, H. (1970)
1. The responses of the post-synaptic membrane of sympathetic ganglion cells to noradrenaline (NA) and to acetylcholine (ACh) were studied in relation to the slow inhibitory post-synaptic potential (S-IPSP) and slow excitatory one (S-EPSP) respectively. 2. NA produced an hyperpolarization of about 4 mV in cells of rabbit superior cervical ganglia. 3. The hyperpolarizing response to NA was not accompanied by any detectable change in membrane resistance, and it was depressed by conditioning depolarization. 4. NA also depressed all the post-synaptic potentials, presumably by an action on presynaptic function. 5. ACh produced a large depolarization in ganglion cells of rabbit and of frog (paravertebral) ganglia, which was accompanied by a large decrease in membrane resistance. 6. When ACh was applied during nicotinic blockade, achieved with high concentration of nicotine (frog ganglia) or D-tubocurarine (rabbit ganglia), it still produced a considerable depolarization. This response could be blocked by atropine, and is presumably a muscarinic type of action. 7. The muscarinic-ACh response was not accompanied by a decrease in membrane resistance. Instead, the frog ganglion cells exhibited increased resistances of up to more than twice the resting value during both the muscarinic-ACh depolarization and the S-EPSP. 8. The muscarinic-ACh depolarization and the S-EPSP were both depressed by conditioning hyperpolarization (in nicotinized frog cells). An initial hyperpolarizing phase now appeared in both of these responses. 9. It is concluded that the hyperpolarizing response to NA and the depolarizing response to muscarinic-ACh action are not generated by increases in ionic mobilities in the post-synaptic membrane; and that these two responses are produced by the same electrogenic mechanisms which underlie the S-IPSP and the S-EPSP respectively.